Hubungan Frekuensi Konsumsi Minuman Teh Kemasan dengan Status Gizi Remaja di SMKN 1 Purwokerto - Nesya Anggita Rahmadhani; Farida Nur Isnaeni; Siti Zulaekah (Yayasan Literasi Sains Indonesia, 2026)
Adolescence is a period of rapid growth that requires optimal nutritional intake. However, changes in lifestyle and consumption patterns among adolescents often lead to a habit of consuming sugar-sweetened beverages, including packaged tea that contains relatively high amounts of sugar. Excessive sugar consumption can increase daily energy intake and potentially lead to nutritional problems, particularly overweight and obesity. This study aims to determine the relationship between the frequency of packaged tea consumption and the nutritional status of adolescents at SMKN 1 Purwokerto. This study employed an analytical observational design with a cross-sectional approach. The study population consisted of all 179 10th-grade AKL students at SMKN 1 Purwokerto, with a sample of 123 students selected using proportionate random sampling. Data on the frequency of packaged tea consumption were collected using a Food Frequency Questionnaire (FFQ), while nutritional status data were obtained through measurements of weight and height, which were then analyzed using the BMI/U indicator based on z-scores. The data were subsequently analyzed to test the relationship between the two variables using the Chi-Square correlation test. The results of the study showed no association between the consumption of packaged tea beverages and the nutritional status of adolescents (p-value = 0.204; p > 0.05). Thus, the consumption of packaged tea beverages does not affect nutritional status.